Research of the Dynamic Characteristic Analysis of Auto Transmission Housing - Meng Fanlong; Ma Weijin; Zhang Jiping; Luo Chaoyang; Yang Wei; Zhang Yanlong (Jixie chuandong)
To understand the structure dynamic characteristic problem of a certain type auto transmission housing,taking the type auto transmission housing as the research object,the modal simulation analysis and the experimental modal analysis are respectively carried out on the transmission housing by using the research method combining the technologies of mechanical structure finite element analysis and experimental modal analysis.The dynamic parameters of the transmission housing are extracted,the results of simulation and experiment are compared,it shows the change trend of first six order modal vibration mode have a certain similarity degree,with the relative errors of the same modal frequency are within 8%,it is effectively verified that the results of the structure modal simulation analysis on the transmission housing structure is the reliability. At the same time,the simulation and experiment results can effectively reflect the dynamic characteristics of the transmission housing,a foundation for auto transmission housing structure dynamic optimization is laid.